Dynamic processes in biological membrane mimics revealed by quasielastic neutron scattering. (August 2017) - Lautner, Lisa; Pluhackova, Kristyna; Barth, Nicolai K.H.; Seydel, Tilo; Lohstroh, Wiebke; Böckmann, Rainer A.; Unruh, Tobias
Highlights: Review on the molecular dynamics in biological membrane mimics as revealed by neutron scattering. Fundamental molecular mechanism of lateral lipid diffusion. Influence of additives and proteins on the short-time dynamics of lipids. Comparison of recent neutron scattering and MD simulation data with respect to molecular membrane dynamics. Abstract: Neutron scattering is a powerful tool to study relaxation processes in biological membrane mimics in space and time. Combining different inelastic and quasielastic neutron scattering techniques, a large dynamic range can be covered: from atomic to mesoscopic lengths and from femto- to some hundreds of nanoseconds in time. This allows studies on e.g. the diffusion of lipids, the membrane undulation motions, the dispersion of sound waves in membranes as well as the mutual interactions of membrane constituents such as lipids, proteins, and additives. In particular, neutron scattering provides a quite direct experimental approach to the inter-atomic and inter-molecular potentials on length and time scales which are perfectly accessible by molecular dynamics (MD) simulations. Neutron scattering experiments may thus substantially support the further refinement of biomolecular force fields for MD simulations by supplying structural and dynamical information with high spatial and temporal resolution. In turn, MD simulations support the interpretation of neutron scattering data. The combination of both, neutron scattering experiments and MD simulations, yields an unprecedented insight into the molecular interactions governing the structure and dynamics of biological membranes. This review provides an overview of the molecular dynamics in biological membrane mimics as revealed by neutron scattering. It focuses on the latest findings such as the fundamental molecular mechanism of lateral lipid diffusion as well as the influence of additives and proteins on the short-time dynamics of lipids. Special emphasis is placed on the comparison of recent neutron scattering and MD simulation data with respect to molecular membrane dynamics on the pico- to nanosecond time scale.